2023
DOI: 10.3390/foods12061146
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Networking-Guided Isolation of a Phenolic Constituent from Prunus mume Seed and Its Antioxidant and Anti-Inflammatory Activities

Abstract: Prunus mume (Maesil) is used in health foods and alternative medicine in Korea. In the present study, the anti-inflammatory and antioxidant effects of phenolics from P. mume seed extracts were examined. First, the biological activities of various P. mume extracts were evaluated, and the profiles of their chemical compounds were investigated by Global Natural Products Social (GNPS)-molecular networking. Among these extracts, fermented Maesil seed extract (FMSE) showed potent anti-inflammatory and antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…NAP performs in silico fragmentation-based metabolite predictions or annotations of candidate structures through searching several databases including GNPS, ChEBI (Chemical Entities of Biological Interest), SUPER NATURAL (II) and DNP. Therefore, using these two scoring methods, NAP is a beneficial tool when experimental spectra are matched to a few spectral libraries matches as it also allows the propagation of annotations in the absence and presence of library spectral matches (da Silva et al, 2018; Nephali et al, 2022; Kim et al, 2023). The The outputs of the NAP obtained in this study are reported in the supplementary material.…”
Section: Resultsmentioning
confidence: 99%
“…NAP performs in silico fragmentation-based metabolite predictions or annotations of candidate structures through searching several databases including GNPS, ChEBI (Chemical Entities of Biological Interest), SUPER NATURAL (II) and DNP. Therefore, using these two scoring methods, NAP is a beneficial tool when experimental spectra are matched to a few spectral libraries matches as it also allows the propagation of annotations in the absence and presence of library spectral matches (da Silva et al, 2018; Nephali et al, 2022; Kim et al, 2023). The The outputs of the NAP obtained in this study are reported in the supplementary material.…”
Section: Resultsmentioning
confidence: 99%
“…NAP performs in silico fragmentation-based metabolite predictions or annotations of candidate structures through searching several databases including GNPS, ChEBI (Chemical Entities of Biological Interest), SUPER NATURAL (II) and DNP. Therefore, using these two scoring methods, NAP is a beneficial tool when experimental spectra are matched to a few spectral libraries matches as it also allows the propagation of annotations in the absence and presence of library spectral matches (da Silva et al, 2018 ; Nephali et al, 2022 ; Kim et al, 2023 ). The outputs of NAP obtained in this study are reported in the supplementary material.…”
Section: Resultsmentioning
confidence: 99%